Silenciamento e tomada de palavra: ambivalências discursivas em pronunciamentos de Evo Morales e Lula da Silva - Pereira, Maísa Ramos (2019)
In this work, based on materialist Discourse Analysis, we analyze linguistic formulations of Evo Morales and Lula da Silva, extracted from their respective first presidential inaugurations. We discuss issues concerning discursive processes involving the silencing of minority majorities and the word-of-mouth of their spokespersons. The emergence of representative rulers of majorities allows us to observe how exclusionary the "democratic" regime is: centuries have gone by until representatives with characteristics of historically marginalized social segments who embodied language, body and voice of those who could supposedly exercise their sovereignty under democracy. In this sense, we seek to understand the historical and discursive process of the construction of Presidents Evo Morales and Lula da Silva as political representatives, analyzing, in their public statements, constructions of a particular identity and / or generic republican identity, production of conciliations and / or consensuses, marks of historicity of the struggles of social movements and of leaderships that preceded them and that established their respective paths to the presidency of the Republic, relations with opponents and mentions to the poorest segments of the population. Through the taking of words by subjects that emerge from a socially silenced and excluded majority, which succeeds in raising one of their own, our thesis is that ambivalent discursive functions occur in the pronouncements of possession of such historical subjects derived from the oscillation between the events of their political ascents and the political history of their countries, between the popular conquest and the aristocratic concession, between the need to speak of social struggles and not to name opponents. From the silencing to the taking the floor, in the irruption of the discursive event, there are previous histories of struggles as well as imposed silencing, that compete for the ways of saying of such subjects. In such a way, Evo Morales and Lula da Silva carry out the historical narratives of their peoples, while they undergo historical discursive coercions about their speeches. Since discourse is something that struggles and is a power that must be seized, to exercise its right to make itself heard, subjects whose lives are excluded and exploited do not have the public speech with transformative potential at their disposal. It is necessary to take the floor. Thus, the place of speech will contribute to the legitimacy and performative force of what is said by the people and their representatives, because these lines have the foundation and consistency of life and a History of struggles.